Renewable Energy and Economic Growth Nexus: A Case of United Arab Emirates. - Kayani, Farrukh Nawaz (International Journal of Energy Economics and Policy, 2021)
The study empirically examined the relationship between renewable energy consumption and economic growth in case of United Arab Emirates (UAE). We took annual time series data for the variables that include renewable energy consumption, GDP per capita, capital formation, employment, and trade openness for the time period ranging from 1996 to 2018. Initially, we applied the autoregressive distributed lag (ARDL) model for assessing the long-run relationship among the variables. We got confronted with the issue of Multicollinearity as we found the intercorrelations among the independent variables. Therefore, we adopted the alternative approach of Oridnary Least Square technique (OLS) for guaging the relationship between renewable energy and economic growth. We ran two different OLS equations, in the first equation we took renewable energy as dependent and economic growth as independent varibiable. In the second equation, we took economic growth as dependent and renewable energy as independent variable. In both of the cases, the results confirm that there is insignficnat realtionship between renewable energy consumption and economic growth. The reason could be that UAE is primarly dependent upon avaiation, tourism, hotelling, construction and real estate industries for revenues generation. Keywords: Renewable Energy, Sustainable Development, Economic Growth, Fossil Fuels, United Arab Emirates. JEL Classifications:Q01, Q4, Q42 DOI: https://doi.org/10.32479/ijeep.11559